Coat color mismatch improves survival of a keystone boreal herbivore: Energetic advantages exceed lost camouflage. Issue 2 (1st December 2022) - Kennah, Joanie L.; Peers, Michael J. L.; Vander Wal, Eric; Majchrzak, Yasmine N.; Menzies, Allyson K.; Studd, Emily K.; Boonstra, Rudy; Humphries, Murray M.; Jung, Thomas S.; Kenney, Alice J.; Krebs, Charles J.; Boutin, Stan
Abstract: Climate warming is causing asynchronies between animal phenology and environments. Mismatched traits, such as coat color change mismatched with snow, can decrease survival. However, coat change does not serve a singular adaptive benefit of camouflage, and alternate coat change functions may confer advantages that supersede mismatch costs. We found that mismatch reduced, rather than increased, autumn mortality risk of snowshoe hares in Yukon by 86.5% when mismatch occurred. We suggest that the increased coat insulation and lower metabolic rates of winter‐acclimatized hares confer energetic advantages to white mismatched hares that reduce their mortality risk. We found that white mismatched hares forage 17–77 min less per day than matched brown hares between 0°C and −10°C, thus lowering their predation risk and increasing survival. We found no effect of mismatch on spring mortality risk, during which mismatch occurred at warmer temperatures, suggesting a potential temperature limit at which the costs of conspicuousness outweigh energetic benefits.